Ideation Factors on Long-Acting Reversible Contraception Practices Among Family Planning Clients - Handayani, Sarah; Suraya, Izza; Asiah, Nur; Majid, Nurkholis (Poltekkes Kemenkes Jakarta III, 2022)
Ideation is a new way of thinking involving the diffusion of these ideas through social interaction in local, culturally homogeneous communities. Making decisions about behavior depends on ideation factors. This study aimed to determine ideation factors associated with long-acting contraceptive behavior among family planning (FP) clients in East and North Jakarta. The data was derived from the